Efektivitas penerapan model pembelajaran peer teaching terhadap proses pembelajaran PJOK - Silviyani, Selvi Dwi; Sonjaya, Azhar Ramadhan; Permadi, Asep Angga; Hidayat, Hidayat (Jurnal Porkes, 2023)
The results of observations at school, the average value of student learning outcomes is still low and needs to be improved. The purpose of this study was to determine the effectiveness of applying the peer teaching learning model to the PJOK learning process at SMPN 2 Leles Garut. This research uses qualitative and quantitative methods. The population in the study were 30 students. This study used a total sampling technique, because researchers took the entire population. Data analysis in research using PTK, data were analyzed qualitatively, while for quantitative data using the amount of active learning time. The results of the study were in the form of students' understanding tests through a questionnaire. PJOK learning is carried out using the peer teaching learning model which is carried out for 6 meetings in cycle I, to cycle III. Based on the results of the data analysis conducted, it was stated that from the study each cycle experienced a significant increase, in the first cycle 50.30% in the moderate category, in the second cycle 72.37% in the good category, in the second cycle it experienced an increase of 22.07% from the second cycle. I, cycle III 75.55%, with a good category where the increase from cycle II to cycle III was 3.18%. So it can be concluded that the peer teaching learning model has effectiveness in the PJOK learning process